CuCl-catalyzed aerobic oxidation of 2,3-allenols to 1,2-allenic ketones with 1:1 combination of phenanthroline and bipyridine as ligands - Gao, Shuxu; Liu, Yu; Ma, Shengming (Beilstein Journal of Organic Chemistry, 2011)
A protocol has been developed to prepare 1,2-allenyl ketones using molecular oxygen in air or pure oxygen as the oxidant from 2,3-allenylic alcohols with moderate to good yields under mild conditions. In this reaction CuCl (20 mol %) with 1,10-phenanthroline (10 mol %) and bipyridine (10 mol %) was used as the catalyst. It is interesting to observe that the use of the mixed ligands is important for the higher yields of this transformation: With the monoligand approach developed by Markó et al., the yields are relatively lower.
Keywords: allenic ketone; allenol; Cu(I) catalyst; oxidation

Metal-Catalyzed Oxidations of Organic Compounds - Sheldon, R. A.; Kochi, J. K. (Academic Press, 1981)

Comprehensive Organic Synthesis - Trost, B. M.; Fleming, I.; Ley, S. V. (Pergamon, 1991)

(untitled) - Fatiadi, A. J. (Synthesis, 1976)

Chromium Oxidations in Organic Chemistry - Cainelli, G.; Cardillo, G. (Springer, 1984)

Green Cemistry: Theory and Practice - Anastas, P.; Warner, J. (Oxford University Press, 1998)

(untitled) - Blackburn, T. F.; Schwartz, J. (J. Chem. Soc., Chem. Commun., 1977)

(untitled) - Peterson, K. P.; Larock, R. C. (J. Org. Chem., 1998)

(untitled) - Nishimura, T.; Onoue, T.; Ohe, K.; Uemura, S. (J. Org. Chem., 1999)

(untitled) - ten Brink, G. J.; Arends, I. W. C. E.; Sheldon, R. A. (Science, 2000)

(untitled) - Muzart, J. (Tetrahedron, 2003)
for a review

(untitled) - Semmelhack, M. F.; Schmid, C. R.; Cortés, D. A.; Chou, C. S. (J. Am. Chem. Soc., 1984)

(untitled) - Markó, I. E.; Giles, P. R.; Tsukazaki, M.; Brown, S. M.; Urch, C. J. (Science, 1996)

(untitled) - Markó, I. E.; Gautier, A.; Dumeunier, R.; Doda, K.; Philippart, F.; Brown, S. M.; Urch, C. J. (Angew. Chem., Int. Ed., 2004)

(untitled) - Sheldon, R. A.; Arends, I. W. C. E.; ten Brink, G. J.; Dijksman, A. (Acc. Chem. Res., 2002)

(untitled) - Zhan, B.; Thompson, A. (Tetrahedron, 2004)

(untitled) - Marshall, J. A.; Robinson, E. D. (J. Org. Chem., 1990)

(untitled) - Mashall, J. A.; Wang, X. (J. Org. Chem., 1991)

(untitled) - Hashmi, A. S. K. (Angew. Chem., Int. Ed., 1995)

(untitled) - Hashmi, A. S. K.; Schwarz, L.; Choi, J. H.; Frost, T. M. (Angew. Chem., Int. Ed., 2000)

(untitled) - Ma, S.; Zhang, J. (Chem. Commun., 2000)

(untitled) - Ma, S.; Yin, S.; Li, L.; Tao, F. (Org. Lett., 2002)

(untitled) - Ma, S.; Yu, Z. (Angew. Chem., Int. Ed., 2002)

(untitled) - Ma, S.; Zhang, J.; Lu, L. (Chem.–Eur. J., 2003)

(untitled) - Ma, S.; Yu, S.; Yin, S. (J. Org. Chem., 2003)

(untitled) - Ma, S.; Yu, Z. (Chem.–Eur. J., 2004)

(untitled) - Ma, S.; Yu, S. (Org. Lett., 2005)

(untitled) - Ma, S.; Gu, Z.; Yu, Z. (J. Org. Chem., 2005)

(untitled) - Sromek, A. W.; Rubina, M.; Gevorgyan, V. (J. Am. Chem. Soc., 2005)

(untitled) - Dudnik, A. S.; Gevorgyan, V. (Angew. Chem., Int. Ed., 2007)

(untitled) - Marx, V. M.; Burnell, D. J. (Org. Lett., 2009)

(untitled) - Alcaide, B.; Almendros, P.; Martínez del Campo, T. (Eur. J. Org. Chem., 2007)

(untitled) - Sampath, M.; Loh, T.-P. (Chem. Commun., 2009)

(untitled) - Zhao, J.; Loh, T.-P. (Angew. Chem., Int. Ed., 2009)

(untitled) - Russell, S. W.; Weedon, B. C. L. (J. Chem. Soc. D, 1969)

(untitled) - Landor, P. D.; Landor, S. R.; Mukasa, S. (J. Chem. Soc. D, 1971)

(untitled) - Rannulu, N. S.; Rodgers, M. T. (J. Phys. Chem. A, 2007)

(untitled) - Reetz, M. T.; Li, X. (Angew. Chem., Int. Ed., 2005)

(untitled) - Reetz, M. T. (Angew. Chem., Int. Ed., 2008)

(untitled) - Li, J.; Zhou, C.; Fu, C.; Ma, S. (Tetrahedron, 2009)

(untitled) - Mukaiyama, T.; Harada, T. (Chem. Lett., 1981)

(untitled) - Alcaide, B.; Almendros, P.; Aragoncillo, C.; Redondo, M. C. (Eur. J. Org. Chem., 2005)

(untitled) - Yang, Y.; Shen, Z.; Loh, T.-P. (Org. Lett., 2009)

(untitled) - Isaac, M. B.; Chan, T. H. (J. Chem. Soc., Chem. Commun., 1995)

(untitled) - Ma, S.; Yu, S.; Yin, S. (J. Org. Chem., 2003)